Hubungan Pengetahuan Dan Peran Keluarga Sebagai Caregiver Informal Terhadap Perawatan Mandiri Lansia Di Posbindu Wilayah Kerja Puskesmas Megang Kota Lubuklinggau Tahun 2025 - Wilda Firsty Casanova; Yance Hidayat; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The increasing number of elderly people presents challenges in fulfilling self-care needs due to declines in physical, psychological, and social functions. In this context, the family plays an important role as an informal caregiver through knowledge and active involvement in elderly care. Optimal family knowledge and roles are expected to enhance elderly independence in meeting basic needs. This study aimed to determine the relationship between family knowledge and the role of the family as informal caregivers on elderly self-care at the Posbindu in the working area of Megang Public Health Center, Lubuklinggau City. This study employed a quantitative observational analytic design with a cross-sectional approach. The sample consisted of 70 respondents selected from families with elderly members aged ≥60 years. Data were collected using structured questionnaires and analyzed through univariate and bivariate analyses using the Chi-square test. The results showed that most respondents had good levels of knowledge and informal caregiver roles, as well as good levels of elderly self-care. Bivariate analysis indicated a significant relationship between family knowledge and the role of the family as informal caregivers with elderly self-care (p < 0.05). The conclusion of this study indicates that family knowledge and the role of the family as informal caregivers are significantly associated with elderly self-care. Therefore, increasing family education and empowerment is necessary to support elderly independence and improve their quality of life.